Alternativas de poscosecha sobre la calidad en tres variedades de café arábigo - Bravo Bermeo, Carmen Fátima (2018)
The purpose of this degree work was to determine the effect of the types of drying on the organoleptic quality of three varieties of coffee, which are Catucaí, Sarchimor and Bourbón, from this 27 samples were taken with their respective methods of benefit that are: semihumid, enzymatic, and conventional wet, three types of drying were also carried out: sieve, tendal and canvas to reach the optimum humidity of the coffee bean (12%), in La Chorrera enclosure of San Placido parish of Portoviejo Manabí canton, on the Santa Bárbara SA farm To obtain the results of this work we apply the orthogonal Taguchi method, L9 (3) 4 3 levels and 4 factors. In what is the physical quality of the coffee bean, color, smell, shape, moisture content, size, and density were evaluated, physical defects and foreign matter were also considered. The organoleptic characteristics in the coffee cup were also evaluated, with the ten attributes that govern the SCAA standards that are: fragrance / aroma, flavor, residual flavor, acidity, body, uniformity, balance, clean cup, sweetness and taster's score, giving as best treatment the Catucaí 2-SL variety, with the semi-humid benefit method, with a resting time of 30 hours and sieve drying (A1B1C3D1). In the classification of qualities of the Arabic coffees, the best sensory score in the quality of the cup was an expected average of 79.34 points, which is equivalent to a very good cup.